Using the ARCS model to improve undergraduates' perceived information security protection motivation and behavior. (May 2022) - Tsai, Chun-Yen; Shih, Wen-Ling; Hsieh, Fu-Pei; Chen, Yun-An; Lin, Chien-Liang; Wu, Hui-Ju
Abstract: The ARCS (attention, relevance, confidence, and satisfaction) model was used to design an information security (InfoSec) course, and its effects on students' perceived InfoSec protection motivation and their InfoSec behavior were explored. A quasi-experimental design was adopted in this research. The participants were 147 undergraduates who took liberal arts courses in a university in southern Taiwan. There were 68 students in the experimental group and 79 in the control group. The specific teaching strategies of the ARCS model based on the Protection Motivation Theory were used to explore students' learning outcomes. The results of the study revealed that after attending the course that applied the ARCS model, the experimental group students outperformed their counterparts in terms of perceived InfoSec protection motivation (perceived severity, vulnerability, response efficacy, self-efficacy, and response costs). Meanwhile, the experimental group students' self-report frequencies of problematic InfoSec behavior were lower than those of the control group students. These findings imply that InfoSec education using the ARCS model in the liberal arts education courses of universities has potential. Highlights: The ARCS model was used to design an information security (InfoSec) course. The quasi-experiment was conducted to investigate the variations in learning outcomes. The ARCS model led to differences in students' InfoSec protection motivation. The ARCS model resulted in reducing students' problematic InfoSec behavior. InfoSec education using the ARCS model has the potential to be promoted.